Pemberdayaan Perantau Pada Masa Wabah Covid-19 (Studi di Nagari Kapalo Koto Kabupaten Padang Pariaman) - Armaidi Tanjung (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
Migrating has become a tradition in Minangkabau, including for residents of Nagari Kapalo Koto, Nan Sabaris District, Padang Pariaman Regency, West Sumatra Province. The emotional and kinship ties between residents who live in the village and migrants are still very strong. Communication between the people who have been overseas and those in the village is still ongoing. Various developments and development activities in Nagari Kapalo Koto are still communicated through informal information between overseas families and those living in the village (Nagari Kapalo Koto). Entering 2020, Indonesia began to be attacked by the Covid-19 virus outbreak. The impact is very influential on various activities of community life. This includes Nagari Kapalo Koto residents who have experienced the impact of Covid-19. It turned out that Nagari Kapalo Koto's apparatus and nomads played an active role in empowering the people who continued to live in the village during the Covid-19 outbreak. Empowerment of migrants is to help residents of Nagari Kapalo Koto who are affected by Covid-19. So that the assistance provided can ease the burden on the residents of Nagari Kapalo Koto in the midst of various restrictions that must be passed during the Covid-19 outbreak.